Cover Image, Volume 8, Issue 10. Issue 10 (27th October 2020) - Lefort, Émilie C.; Diaconu, Bogdan; Bentley, Victoria L.; Blay, Jonathan
Abstract : The cover image is based on the Original Research Apigenin upregulation of CD26/DPPIV on colon epithelial cells requires inhibition of casein kinase 2 by Émilie C. Lefort et al., https://doi.org/10.1002/fsn3.1823 .